1979
DOI: 10.1159/000149066
|View full text |Cite
|
Sign up to set email alerts
|

A Vesicular Stomatitis Virus (Cytomegalovirus) Pseudotype and Its Use in Neutralization Tests

Abstract: Infection with vesicular stomatitis virus (VSV) of human diploid cells preinfected with the AD-169 strain of human cytomegalovirus (CMV) resulted in the formation of a VSV (CMV) pseudotype. Its formation was favored by increasing the bicarbonate content in doubly-infected cultures. The pseudotype was capable of infecting not only human but also rabbit cells. Pseudotype particles formed after infection with the tl 17 mutant of VSV, which carries a thermolabile lesion in its neutralization antigen, were more sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been reported that human diploid cells productively infected with human eytomegalovirus (HCMV) and superinfected with vesicular stomatitis virus (VSV) result in the formation of VSV (HCMV) pseudotypes (12).…”
mentioning
confidence: 99%
“…It has been reported that human diploid cells productively infected with human eytomegalovirus (HCMV) and superinfected with vesicular stomatitis virus (VSV) result in the formation of VSV (HCMV) pseudotypes (12).…”
mentioning
confidence: 99%
“…
An easy-to-prepare, highly efficient antigen for cervical cancer serologyThere is ample evidence that human papillomaviruses (HPV) are involved in the etiology of cervical cancer (CC) (zur Hausen, 1991). These viruses do not grow in tissue culture.
…”
mentioning
confidence: 99%